Correlation of Elbow Carrying Angle with Height and Forearm Length among Bangladeshi Adolescent - Chowdhury, Urmila; Zahur, Tamanna; Hasem, Jehan; Lina, Roksana Shirin; Roy, Sanchita; Sultana, Abeda (IAHS Medical Journal, 2024)
Background: Carrying angle is a medial acute angle between median axis of the upper arm with the fully extended and supinated forearm. It plays a vital role in carrying objects and keeps upper extremity away from the pelvis during walking and disappears when the forearm is pronated and flexed. It increases with age from childhood to adolescent and is greater in female and in dominant arm; also differs with race, ethnicity and number of anthropometric body parameters. Present study was designed to evaluate the carrying angle in normal adolescents of Bangladesh and to see its correlation with height and forearm length in both sexes. Materials and methods: This cross-sectional analytical study was conducted in the Department of Anatomy, Chittagong Medical College, Chattogram upon 100 male and 100 female adolescents of 10-19 years. After getting permission from the ethical review committee, carrying angle, height and forearm length of the participants were measured by standard method. Recorded data were analyzed by using SPSS version 25. For statistical analysis Pearson’s correlation test was done. p-value was considered significant if it was <0.05 at 95% level of confidence. Results: Carrying angle of both sides in both sexes have shown significant positive correlation with height (p<0.05) but have non-significant positive correlation with forearm length of respective side in both sex (p>0.05). Conclusion: Reference value of carrying angle is essential for management and follows up of supracondylar elbow fracture causing cubitus varus deformity, diagnosis, and treatment of epicondylar disease, elbow implantation and sex determination by forensic experts. IAHS Medical Journal Volume 06(1), June 2023; 68-73